Charles Lever, His Life in His Letters, Vol. I - Lever, Charles, 1806-1872; Downey, Edmund, 1856-1937 (Salt Lake City, UT : Project Gutenberg, 2011)
"Charles Lever, His Life in His Letters, Vol. I" by Edmund Downey is a biographical account based on the letters of the Irish novelist written in the early 20th century. The work provides an intimate look at Lever's life, particularly his literary career, through personal correspondence and anecdotes from friends and family, aiming to present a more nuanced portrait than previous biographies. The opening of the book sets the tone for an exploration of Charles Lever's early life, discussing the confusion surrounding his birthdate and establishing an account of his upbringing in Dublin. Lever$1 (Bs father, James, is introduced as a successful architect, and we learn about the dynamics of his family life, Lever's educational experiences, and early interests in literature and practical jokes. Vivid descriptions of his school days and university life at Trinity College are recounted, showcasing his mischievous nature and foreshadowing his future as a novelist, laying the groundwork for an intriguing exploration of the man behind the stories. (This is an automatically generated summary.)s
Release date is 2011-04-13
Produced by David Widger
Keywords: Lever, Charles James, 1806-1872 -- Correspondence; Novelists, Irish -- 19th century -- Correspondence